Issues of parallel software development for the domain decomposition methods - Gurieva, Y.L.; Perevozkin, D.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2018)
Various aspects of parallel software development for the domain decomposition methods are considered: the application of MPI programming technology for cluster systems, the choice points in the design of parallel programs for the domain decomposition methods, the need to implement a matrix action without its explicit representation, the work with index sets in the software implementation of restriction and continuation operators as well as in the data exchange between subdomains. On a series of numerical experiments for a model problem, the questions of the best choice of the configuration of launching an executable program on a cluster are studied to minimize the computation time and a strategy for performing such experiments is proposed.